Effect of cutting speed and feed in turning hardened stainless steel using coated carbide cutting tool under minimum quantity lubrication using castor oil - Elmunafi, M.; Mohd Yusof, N.; Kurniawan, Denni (2015)
© SAGE Publications Ltd, unless otherwise noted. Manuscript content on this site is licensed under Creative Commons Licenses. Minimum quantity lubrication is a technique to have the advantages that cutting fluids bring yet keeping their use at minimum. For the cutting fluids, inedible vegetable oils are potential for minimum quantity lubrication machining. Castor oil was selected in this study as the cutting fluid for turning of hardened stainless steel (hardness of 47-48 HRC). The hard turning was with minimum quantity lubrication (50 mL/h flow rate and 5 bar air pressure) at various cutting speeds (100, 135, and 170 m/min) and feeds (0.16, 0.20, and 0.24smm/rev). The machining responses were tool life, surface roughness, and cutting forces. Design of experiments was applied to quantify the effects of cutting parameters to the machining responses. Empirical models for tool life, surface roughness, and cutting forces were developed within the range of cutting parameters selected. All machining responses are significantly influenced by the cutting speed and feed. Tool life is inversely proportional to cutting speed and feed. Surface roughness is inversely proportional to cutting speed yet is proportional to feed. Cutting forces are more influenced by feed than by cutting speed. A combination of low cutting speed and feed was the optimum cutting parameters to achieve long tool life, low surface roughness, and low cutting forces.